Identifying priority interventions using the Behaviour Change Wheel to improve public primary school food environments in urban South Africa. (March 2023) - Erzse, Agnes; Karim, Safura Abdool; Rwafa-Ponela, Teurai; Kruger, Petronell; Hofman, Karen Joanne; Foley, Louise; Oni, Tolu; Goldstein, Susan
Abstract: Background: In South Africa, overweight and obesity affects 13% of children and 17% of adolescents. School food environments play a vital role in dietary behaviours and resulting obesity rates. Interventions targeting schools can be effective if evidence-based and context relevant. There are substantial gaps in policy and implementation of government strategies to promote healthy nutrition environments. The aim of this study was to identify priority interventions to improve school food environments in urban South Africa using the Behaviour Change Wheel model. Methods: A multiphased secondary analysis of individual interviews with 25 primary school staff was undertaken. First, we identified risk factors influencing school food environments using MAXQDA software; then deductively coded these using the Capability, Opportunity, Motivation–Behaviour model, which informs the Behaviour Change Wheel framework. To identify evidence-based interventions, we used the NOURISHING framework and matched interventions to risk factors. Last, interventions were prioritised through a Delphi survey, administered to stakeholders (n=38) representing health, education, food service, and not-for-profit sectors. Consensus for priority interventions was defined as an intervention being either somewhat or very important and feasible, with high level of agreement (quartile deviation ≤0·5). Findings: We identified 21 interventions to improve school food environments. Of these, seven were endorsed as important and feasible to enable school stakeholders', policy makers', and children's capability, motivation, and opportunity of having healthier foods within schools. Prioritised interventions targeted a range of protective and risk factors, including issues of affordability and availability of unhealthy foods within school premises. As such, top priority interventions included (1) regulations on what kinds of foods can be sold at schools; (2) compulsory, child-friendly warning labels on unhealthy foods; and (3) training of school staff through workshops and discussions to improve school nutrition environment. Interpretation: This is the first study to use the Behaviour Change Wheel and stakeholder engagement to identify intervention priorities to improve food environments in South African schools. Prioritisation of evidence-based, feasible, and important interventions that are underpinned by behaviour change theories is an important step towards enhanced policy making and resource allocation to effectively tackle South Africa's childhood obesity epidemic. Funding: This research was funded by the National Institute for Health Research (NIHR; grant number 16/137/34) using UK Aid from the UK Government to support global health research. AE, PK, TR-P, SG, and KJH are supported by the SAMRC/Wits Centre for Health Economics and Decision Science–PRICELESS SA (grant number 23108).